2020
DOI: 10.1002/alr.22664
|View full text |Cite
|
Sign up to set email alerts
|

Serum eosinophil cationic protein: a prognostic factor for early postoperative recurrence of nasal polyps

Abstract: Background The objective of this work was to assess the efficacy of serum eosinophil cationic protein ECP concentration in predicting early postoperative recurrence in patients with chronic rhinosinusitis with nasal polyps CR-SwNP Methods We prospectively enrolled CRSwNP patients to receive bilateral functional endoscopic sinus surgery FESS and followed them for year Serum ECP level was measured within week before surgery Demographics and associated medical factors were analyzed with the surgical outcome and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The patients with ECRS or CRS with nasal polyps have been shown to have a significantly higher level of ECP in nasal tissue than patients with non-eosinophilic CRS and control patients [ 33 34 ]. In addition, serum ECP may be a feasible predictor for early postoperative recurrence of nasal polyps [ 35 ]. That evidence suggested that ECRS pathophysiology does not depend on the mere presence of eosinophil but on the degranulation of eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…The patients with ECRS or CRS with nasal polyps have been shown to have a significantly higher level of ECP in nasal tissue than patients with non-eosinophilic CRS and control patients [ 33 34 ]. In addition, serum ECP may be a feasible predictor for early postoperative recurrence of nasal polyps [ 35 ]. That evidence suggested that ECRS pathophysiology does not depend on the mere presence of eosinophil but on the degranulation of eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that IL-5 and eosinophil cationic protein are ideal biomarkers for predicting the efficacy of clinical treatment for chronic rhinosinusitis with nasal polyps; 28 furthermore, serum eosinophil cationic protein is a useful indicator for predicting the early recurrence of nasal polyps. 29 A double-blind clinical trial confirmed that oral glucocorticoid therapy reduced the levels of IL-5 and eosinophil cationic protein in nasal secretions from patients with chronic rhinosinusitis with nasal polyps. 30 In our study, after stratification of patients with chronic rhinosinusitis with nasal polyps according to peripheral blood eosinophil percentage, we found that the use of glucocorticoids did not significantly reduce the levels of IL-5 or eosinophil cationic protein in peripheral blood and nasal secretions from patients with non-eosinophilic chronic rhinosinusitis with nasal polyps.…”
Section: Discussionmentioning
confidence: 88%
“…Endoscopic sinus surgery was performed for CRS management, applying a bidirectional method that combines anterior-to-posterior and posterior-to-anterior approaches 21 . After surgery, all patients were scheduled for regular follow-ups at our outpatient department as previously described 22 . Briefly, patients were treated with Augmentin ® 30 mg/kg/day for 1 week postoperatively, and at 2 weeks after surgery, nasal corticosteroid spray (mometasone furoate, 200 μg/day) and nasal saline irrigation (250 ml once daily) were initiated for 3 months.…”
Section: Methodsmentioning
confidence: 99%